2021
DOI: 10.1080/21655979.2021.1983975
|View full text |Cite
|
Sign up to set email alerts
|

Interference with lysophosphatidic acid receptor 5 ameliorates oxidized low-density lipoprotein-induced human umbilical vein endothelial cell injury by inactivating NOD-like receptor family, pyrin domain containing 3 inflammasome signaling

Abstract: Endothelial cell damage induced by oxidized low-density lipoprotein (ox-LDL) plays an important role in the pathogenesis of atherosclerosis (AS). We aimed to explore the effects of lysophosphatidic acid receptor 5 (LPAR5) on ox-LDL-induced damage of human umbilical vein endothelial cells (HUVECs). After HUVECs exposed to ox-LDL, LPAR5 expression was detected by RT-qPCR and western blotting. Then, LPAR5 was silenced and cell viability was determined with a CCK-8 assay. ELISA was employed to analyze the contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Lysophosphatidic acid receptor 5 (LPAR5) overexpression is involved in mediating thyroid cancer progression; however, the mechanism underlying this process requires further elucidation ( 69 , 70 ). Additionally, LPAR5 is reportedly associated with lysophosphatidic acid-induced pro-inflammatory signaling cascades in microglia ( 71 73 ). Therefore, LPAR5 may be involved in a common pathway between HT and PTC, which represents a promising area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidic acid receptor 5 (LPAR5) overexpression is involved in mediating thyroid cancer progression; however, the mechanism underlying this process requires further elucidation ( 69 , 70 ). Additionally, LPAR5 is reportedly associated with lysophosphatidic acid-induced pro-inflammatory signaling cascades in microglia ( 71 73 ). Therefore, LPAR5 may be involved in a common pathway between HT and PTC, which represents a promising area of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, postoperative care, rehabilitation training and health education following atherosclerosis bypass grafting is important in improving the quality of life of patients and preventing poor prognoses. As previously stated, inflammation, oxidative stress and endothelial cell dysfunction triggered by the accumulation of ox-LDL in the vascular lining is the common basis for the pathological changes observed in atherosclerosis [ 19 ]. The findings of the present study showed that PDIA3 is a key biological factor in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins were collected using RIPA buffer (Thermo Scientific, CA, USA) and then quantified for protein quantification by using Pierce™ BCA Protein Quantification Kit (Thermo Scientific) [ 15 ]. Protein (20 μg) was used for electrophoresis loading SDS-PAGE and transferred onto PVDF membranes (Millipore, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%